Pengaruh PAD, Dana Perimbangan, SiLPA, Kemiskinan dan Pengangguran terhadap Indeks Pembangunan Manusia dengan Alokasi Belanja Modal sebagai Variabel Intervening (Studi pada Kabupaten/Kota Provinsi Sumatera Selatan) - Verawaty Verawaty; Siti Salwa (Jurnal Bina Akuntansi, 2023)
Human development is a process of expanding choices for humans, especially in accessing development results and achieving human development goals. This can be seen from the HDI. This study aims to analyze PAD, DAU, DAK, DBH, SilPA, Poverty and Unemployment which affect HDI through capital expenditure as an intervening variable. This study used path analysis with SPSS and the Sobel test. The results of the study, namely PAD and unemployment have a significant effect on HDI. DAU, DAK, DBH, SiLPA, Poverty have no significant effect on HDI. DAK, DBH, Poverty have a significant effect on Capital Expenditures and PAD have no significant effect on Capital Expenditures. DAU SiLPA, unemployment has no significant effect on capital expenditure but capital expenditure does not intervene in all research variables. From the results of the conclusion, the government pays more attention to efforts to increase the HDI both through capital expenditure and other fund allocations